Designing and Optimization of Lipid-Based Nanocarriers for Safer and Effective Oral Delivery of Tizanidine Hydrochloride - Pandey, Sharad Prakash (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: The oral route is widely favored for drug delivery due to its simplicity. However, after oral administration, the effectiveness of tizanidine hydrochloride (TZN) is limited due to its low solubility and increased metabolism. The present study investigates the utility of nanostructured lipid carriers (NLCs) as an oral formulation for TZN to boost its therapeutic effectiveness. Materials and Methods: TZN-loaded NLCs were prepared by the solvent evaporation method using glyceryl monostearate and oleic acid as solid and liquid lipids, respectively, while the combination of tween 80 and poloxamer 188 was used as surfactants. The formulation optimization was carried out using a Box–Behnken design taking particle size and entrapment efficiency as response variables. The optimized formulation underwent evaluation for particle size, polydispersity index (PDI), ζ-potential, morphological studies, entrapment efficiency, permeability, and drug release characteristics. Results: The final optimized formulation exhibited all the necessary attributes, including a particle size of 320.6 ± 13.86 nm, PDI of 0.376 ± 0.031, a zeta potential of −25.8 mV, and entrapment efficiency of 78.33% ± 1.96%. In vitro release studies have also demonstrated substantial drug release profiles, highlighting the potential of NLCs for enhanced drug delivery with extendedrelease profiles. Conclusion: The above findings signify that the current optimization model can be used for the development of NLCs for safer and effective oral delivery of TZN which have all the necessary pharmaceutical attributes and may be a promising avenue for its safer and more effective delivery for such drugs.